Biolarvicidal Potentials of the Methanolic-Leaf-Extracts of Selected Tropical Plant Species - Patrick B. Solomon; Ayodele A. Oyedeji; Frankland O. Briyai; Dorcas D. S. Bawo; Jasper F.N Abowei (Journal of Experimental and Clinical Toxicology, 2019)
The global impact of malaria and challenges encountered during its control have necessitated the application of multifaceted strategies, including the application of plant-derived agents. Amidst these challenges the proliferation of the vector is becoming hyperendemic in tropical region. This research is focused on the biolarvicidal activities of the methanolic leaf-extracts of Cassia alata, Microdesmispuberula¸ and Spilanthesfilicaulis against mosquito larva. The mosquito larva were assayed in a static non-renewal test. Results showed no mortality for the negative control, and total mortality for the positive control (p<0.05). The C. alata bioassay was the most active with LC50 value of 13.73 ppm, followed by; M. puberula(21.24 ppm), and S. filicaulis (28.86 ppm). This study concludes that methanolic-leaf-extracts of C. alata, M. puberula¸ and S. filicaulis can be recommended for the formulation of biolarvicide for the control of malaria.
Keywords: Mosquito